2019
DOI: 10.1155/2019/5267025
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus, Nonalcoholic Fatty Liver Disease, and Conjugated Linoleic Acid (Omega 6): What Is the Link?

Abstract: Background and Objective. Type 2 DM and obesity are the coming epidemics and their association with NAFLD is well established; essential fatty acids are vital for body health yet the body cannot make them; 2 essential fatty acids are especially important: linoleic (omega-6) and alpha-linoleic (omega-3) acids; they can be considered as “bioactive lipids” and serve as functional foods. Methods. 50 type 2 Egyptian diabetic patients controlled on oral hypoglycemic drugs together with 20 age- and sex-matched health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The study found that the risk of NAFLD was increased in Type 2 diabetes mellitus, while NAFLD can also be an independent risk factor for the progression of diabetes mellitus [22][23] , thus forming a vicious circle.The speci c prevalence of NAFLD is still unknown, depending on the method used for screening, which is lower when liver transaminase and/or liver ultrasound are used, and higher with gold standard magnetic resonance spectroscopy (MRS). The prevalence of NAFLD in industrialized countries is believed to be between 40% and 50%, and even higher in patients with T2DM, with a prevalence of up to 90% in morbidly obese patients [24][25][26] .…”
Section: Discussionmentioning
confidence: 95%
“…The study found that the risk of NAFLD was increased in Type 2 diabetes mellitus, while NAFLD can also be an independent risk factor for the progression of diabetes mellitus [22][23] , thus forming a vicious circle.The speci c prevalence of NAFLD is still unknown, depending on the method used for screening, which is lower when liver transaminase and/or liver ultrasound are used, and higher with gold standard magnetic resonance spectroscopy (MRS). The prevalence of NAFLD in industrialized countries is believed to be between 40% and 50%, and even higher in patients with T2DM, with a prevalence of up to 90% in morbidly obese patients [24][25][26] .…”
Section: Discussionmentioning
confidence: 95%
“…The reduction of CLA in NAFLD and diabetic obese patients demonstrated the correlation between CLA and regulation of energy metabolism and maintenance of metabolic homeostasis in the liver [ 71 ]. CLA can also induce significant changes in the fatty acid profile of the liver [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study 18 (34.62%) had normal BMI, 19 (36.54%) patients were overweight (25-30 Kg/m 2 ) and 15 (28.85%) were Obese (≥ 30 Kg/m 2 ). 6 Kyung-Soo Kim et al(2019), mentioned in his review article that Saroglitazar reduced alkaline phosphatase as well as triglyceride levels. 4 A review article by Kaul et al(2019), also stated that Saroglitazar was found effective in lowering ALT levels and improving fatty liver (evaluated by…”
Section: Discussionmentioning
confidence: 99%